Níveis de extrato etéreo e suplementação energética para bovinos de corte terminados a pasto - Damasceno, Matheus Leonardi (2018)
The objective of this study was to evaluate the effects of different amounts of supplement and ethereal extract on characteristics nutritional, behavioral and performance of Nellore steers in the finishing phase managed in tropical pasture. Twenty-seven young bulls of the Nellore, mean age of 22 months and mean body weight of 439.3 ± 27.8 kg were used. The experimental design was completely randomized with four treatments in a 2x2 factorial arrangement. Two levels of ethereal extract (LEE = 28g and HEE = 42g / kg of DM) were tested in two levels of supplementation (Lower Sup = 4g) / kg of the BW and High above = 8g / kg of BW). The means were submitted to analysis of variance and compared by orthogonal contrasts. The high supplementation provided higher (P<0.10) consumption of non-fibrous carbohydrates and lower forage consumption. However, total dry matter intake was not influenced (P>0.10). The high level of ethereal extract reduced (P<0.10) the coefficients of dry matter, neutral detergent fiber, total carbohydrates, non - fibrous carbohydrates and organic matter. High supplementation resulted in greater weight gain, reduction in grazing time and in nitrogen concentrations and excretions (P<0.10). The higher amounts of supplement reduce intake forage and increase the performance of beef cattle kept on pasture. The use of soybean as an ingredient in diets of cattle to pasture is an alternative to reduce the amount of supplement offered without interfering with the consumption of forage.